Assisted reproductive technology for women with endometriosis, a clinically oriented review. Issue 3 (June 2021) - Ata, Baris; Telek, Savci Bekir
Abstract : Purpose of review: To discuss optimal management of an assisted reproductive technology (ART) cycle in women with endometriosis. Recent findings: New studies involving euploid embryo transfers provide more insight on the etiology of endometriosis-associated infertility. Oocyte competence to reach live birth seems unlikely to be affected by the disease. Routine medical or surgical treatment prior to an ART cycle does not appear beneficial. Short gonadotropin releasing hormone (GnRH) antagonist or progestin primed ovarian stimulation protocols seem to be proper first choices, depending on the intention for a fresh embryo transfer. Low-quality evidence supports frozen thawed over fresh embryo transfer. Ovarian stimulation for ART does not seem to be associated with symptom progression or recurrence. Summary: How endometriosis affects fertility is still unclear, but ART is an effective pragmatic treatment. Each woman with endometriosis must be assessed with a holistic approach, and in the absence of an indication for otherwise, ART cycles can be kept simple with patient-friendly protocols. Whether a frozen embryo transfer is better than a fresh one should be investigated.